2000
DOI: 10.1089/mdr.2000.6.223
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-ResistantStaphylococcal aureusEvolution in Australia Over 35 Years JOHN D. TURNIDGE and JAN M. BELL

Abstract: Australia has a long association methicillin-resistant Staphylococcus aureus (MRSA). Its unique geographic and demographic features have led to the emergence and spread of three types of MRSA over 35 years. Classical multiresistant hospital-acquired MRSA were first noted in Australia in 1965. By the end of the 1970s, strains of this type of MRSA were well established in the complex tertiary care hospitals in the capital cities on the eastern seaboard of mainland Australia. Characterized by resistance to /3-lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Nationwide surveillance for invasive MRSA infections conducted in the United States reported about 94,000 cases resulting in approximately 18,000 deaths (Klevens et al, 2007). Worldwide, rates of MRSA have been increasing as observed from data obtained via surveillance initiatives by the National Nosocomial Surveillance System (NNIS) and the European Antimicrobial Resistance Surveillance System (EARSS) (Fridkin et al, 2002; Grundmann et al, 2006; Tiemersma et al, 2004; Turnidge & Bell, 2000). Nevertheless, a major concern is the lack of data in many countries, particularly the developing countries, as this could potentially result in global transmission of undetected MRSA strains (Azeez-Akande, 2010; Molton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nationwide surveillance for invasive MRSA infections conducted in the United States reported about 94,000 cases resulting in approximately 18,000 deaths (Klevens et al, 2007). Worldwide, rates of MRSA have been increasing as observed from data obtained via surveillance initiatives by the National Nosocomial Surveillance System (NNIS) and the European Antimicrobial Resistance Surveillance System (EARSS) (Fridkin et al, 2002; Grundmann et al, 2006; Tiemersma et al, 2004; Turnidge & Bell, 2000). Nevertheless, a major concern is the lack of data in many countries, particularly the developing countries, as this could potentially result in global transmission of undetected MRSA strains (Azeez-Akande, 2010; Molton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that MRSA has caused about 94360 severe infections and 18650 in-hospital deaths in 2005 in USA [3] . There were more reports about increasing incidence of MRSA from other countries [4] , [5] . MRSA infection in China is also very severe.…”
Section: Introductionmentioning
confidence: 99%